Influence of mechanical uncertainties on dynamic responses of a full-scale all-FRP footbridge. (1st September 2019) - Wei, Xiaojun; Wan, Hua-Ping; Russell, Justin; Živanović, Stana; He, Xuhui
Abstract: This paper aims to determine the effects of uncertainties in the mechanical properties of FRP composites on the dynamic responses of a full-scale all-FRP bridge. The novelty of the study is in determining the effects that the uncertainties have on the global structural scale properties rather than component properties often studied in literature. To achieve this aim, both uncertainty quantification and global sensitivity analysis are performed using a computationally cost-effective approach based on the polynomial chaos expansion. The results reveal that a coefficient of variation (COV) of 10% for four mechanical parameters can lead to COVs of 3.37%, 2.92% and 3.07% for natural frequencies, COVs of 2.98%, 0.04% and 0.61% for modal masses (corresponding to unity-scaled mode shapes) of the first lateral, first vertical and second vertical modes, and COV of 0.93% for the absolute peak acceleration. The effect of uncertainties, therefore, is very small for the considered excitation case and it could be neglected in the design. In addition, it was found that the longitudinal elastic modulus and shear modulus of the panel are the most influential mechanical parameters in dynamic analysis.